Reinforcing Native Solid‐Electrolyte Interphase Layers via Electrolyte‐Swellable Soft‐Scaffold for Lithium Metal Anode (Adv. Energy Mater. 16/2023). Issue 16 (26th April 2023) - Bae, Jaehyeong; Choi, Keonwoo; Song, Hyunsub; Kim, Do Heung; Youn, Doo Young; Cho, Su‐Ho; Jeon, Dogyeong; Lee, Jiyoung; Lee, Junyoung; Jang, Wontae; Lee, Changhyeon; Kim, Youson; et al.
Abstract : Lithium Metal Anodes In article number 2203818, Sung Gap Im, Il‐Doo Kim, and co‐workers present an innovative approach to stabilize lithium metal anodes using an electrolyte‐swollen solvogel. The solvogel, synthesized on the lithium metal through an initiated chemical vapor deposition process, accommodates the native solid‐electrolyte interphase and offers mechanical reinforcement. This approach effectively suppresses lithium dendrite growth and achieves a record‐high transference number and battery cycle life.